2020
DOI: 10.1038/s41598-020-65764-w
|View full text |Cite
|
Sign up to set email alerts
|

Urine Neutrophil Gelatinase-associated Lipocalin (NGAL) for Prediction of Persistent AKI and Major Adverse Kidney Events

Abstract: We aimed to determine whether urinary neutrophil gelatinase-associated lipocalin (uNGAL) can accurately predict persistent AKI, major adverse kidney events at 30 days (MAKE30) and 365 days (MAKE365) in hospitalized AKI patients. This is a retrospective study of adult patients who were admitted at King Chulalongkorn Memorial Hospital. We performed multivariable logistic regression for persistent AKI, MAKE30, and MAKE365. We developed equations for predicting MAKE30 and MAKE365 and divided the dataset into deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
0
20
1
1
Order By: Relevance
“…Under normal physiological conditions, NGAL has stable low expression in a variety of organs, including the bone marrow, stomach, and colon. A study by Lumlertgul et al [ 20 ] found that, in patients with renal impairment, NGAL values were well outside the normal range values while serum creatinine was still in the normal range, which suggests that NGAL has a high application value for early diagnosis of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, NGAL has stable low expression in a variety of organs, including the bone marrow, stomach, and colon. A study by Lumlertgul et al [ 20 ] found that, in patients with renal impairment, NGAL values were well outside the normal range values while serum creatinine was still in the normal range, which suggests that NGAL has a high application value for early diagnosis of AKI.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Using the data of 1322 AKI patients’ registry at King Chulalongkorn Memorial Hospital, Nuttha et al also demonstrated that uNGAL was associated with pAKI as well as prognosis of AKI patients. 30 In addition, several factors have been shown to be associated with pAKI in previous studies. Firstly, comorbidities, especially for patients with pre-existing renal dysfunction, were associated with longer AKI duration.…”
Section: Discussionmentioning
confidence: 93%
“…6,7,20 Renal function that does not return to normal within 48 h was defined as persistent AKI by the ADQI in 2017. Subsequent studies showed that the morbidity of persistent AKI in critically ill patients is up to 45%-76.9%, 4,5,8,15,21,22 and the ICU mortality rate is 33.1-34%. 5,8 Our study found that the morbidity of persistent AKI was 60.43%, which is similar to the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%